2015
DOI: 10.5539/ijef.v7n11p94
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Income among Real Estate Salespersons: The Impacts of Individual Conditions, Franchises, and Regular Chains

Abstract: <p>This study explores the factors that affect the incomes of real estate salespersons by applying hierarchical linear modeling (HLM) to investigate the incomes of real estate salespersons in Kaohsiung. A total of 510 questionnaires were distributed to large chain housing agencies, of which a total of 319 effective samples were retrieved from 54 branch stores, for an effective return rate of 62.55%. The empirical results showed that individual incomes vary significantly from store to store. About 4.8% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It is hard to find occupations to compare brokerage with (Benjamin et al, 2007;Lee et al, 2015). Still, brokers are undoubtably within sales, and sales force turnover is acknowledged as problematic.…”
Section: Previous Studies 21 Employee and Occupational Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…It is hard to find occupations to compare brokerage with (Benjamin et al, 2007;Lee et al, 2015). Still, brokers are undoubtably within sales, and sales force turnover is acknowledged as problematic.…”
Section: Previous Studies 21 Employee and Occupational Turnovermentioning
confidence: 99%
“…It is hard to find occupations to compare brokerage with (Benjamin et al. , 2007; Lee et al. , 2015).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Longer hours of work indicate a higher investment of effort into work, which means better individual performance. Sirmans and Turnbull (1997), Yu (2001), Lee and Shen (2007), and Lee et al (2015) indicated that longer hours of work led to higher income and better performance. This study predicted that the hours of work coefficient was a positive value.…”
Section: Variable Definition Explanationmentioning
confidence: 99%